Transcatheter implantation of SAPIEN 3 valve in native right ventricular outflow tract for severe pulmonary regurgitation following tetralogy of fallot repair. Issue 1 (4th March 2016) - Rockefeller, Toby; Shahanavaz, Shabana; Zajarias, Alan; Balzer, David
Abstract : Pulmonary valve replacement (PVR) is indicated in patients with significant pulmonary regurgitation (PR), stenosis (PS), or mixed pulmonary valve disease. While once an exclusively surgical procedure, many patients can undergo transcatheter PVR (TPVR) with excellent early outcomes (Haas et al. 2013, Clin. Res. Cardiol. Off. J. German Cardiac Soc. 102:119–128; Kenny et al. 2011, J. Am. Coll. Cardiol. 58:2248–2256; Cheatham et al. Circulation 2015, 131:1960–1970). The available transcatheter options continue to expand, but the majority of cases performed in the United States involve the use of FDA approved Melody valve (Medtronic; Minneapolis, MN) or the SAPIEN (Edwards Lifesciences; Irvine, CA) family of valves. The SAPIEN 3 valve (S3) recently received FDA approval for transcatheter aortic valve replacement. We report the first S3 implantation in the pulmonary position for treatment of chronic pulmonary regurgitation and progressive right ventricular dilation in an 18 year old male with repaired Tetralogy of Fallot. © 2016 Wiley Periodicals, Inc.